Daugiakultūrių miestų paveldas: interpretacijos problemos ir galimybės - Čepaitienė, Rasa (Lietuvos istorijos studijos, 2008)
In the article, the conceptions that have influenced (and still are influencing) appreciation, assimilation, and usage of the heritage accumulated in Lithuanian historical towns are analyzed, and some potential ways of solving the arising problems are proposed. It is emphasized that recognition, usage, and interpretation of cultural values accumulated in historical towns, which are, as a rule, multi-ethnic, multi-confessional, and multi-cultural, are a complex undertaking and a competence-, creativity-, and responsibility-requiring process.The relationship of such a multipartite problem with the cultural politics of modern Lithuania is examined. Two attitudes, mono-perspective (nationalistic) and multi-perspective (postmodern), towards the relation of ethnic communities and prevailing culture are distinguished. The most lucid cases of heritage appropriation/assimilation, which provoked interethnic or intersectional conflicts of recent times, are analyzed. These are related to the sensitivity of historical memory, which is linked with traumas and wrongs of the recent past.The strategic possibilities of using cultural riches accumulated in our historic towns are treated, referring to the ideas of conservation theorists such as G.J. Ashworth, J.E. Tunbridge, and others ("inclusivist," minimalist, localizing models proposed by them) and taking into account Lithuanian particularity. The actuality of multicultural traditions and experiences of the unique concord in the Great Duchy of Lithuania, considering the present circumstances of a global world, is emphasized.